Love riddles, couple formation, and local identity in Eastern France - Hopkin, D (SAGE Publications, 2003)
The purpose of this article is to show how specific aspects of the popular culture of Lorraine (eastern France) can be linked to distinctive features of the region's historical demography after the Thirty Years War. It examines two customs associated with courtship: the dâyage, an exchange of riddle-like verses between groups of men and women at winter wakes, and the dônage, mock banns of marriage called by young men on the first Sunday of Lent. Both will be shown to have encouraged particularly high levels of geographical endogamy and premarital fertility, while the metaphors of monetary exchange that ran through both the dâyage and dônage into the marriage service itself encouraged social homogany. These customs served as a language in which rural Lorrainers between the seventeenth and the twentieth century could analyze and discuss their demographic strategies. The article considers the role of local elites (political before the Revolution, literary after) in fostering these customs and turning them into a badge of Lorrainer identity.